Deeply Infiltrating iRGD‐Graphene Oxide for the Intensive Treatment of Metastatic Tumors through PTT‐Mediated Chemosensitization and Strengthened Integrin Targeting‐Based Antimigration. Issue 16 (16th June 2021) - Wang, Honglan; Zhou, Jiyuan; Fu, Ying; Zheng, Yuzhao; Shen, Weiyang; Zhou, Jianping; Yin, Tingjie
Abstract: A limited infiltration and the subsequent low effective drug concentration result in poor chemotherapeutic outcomes against tumors, and even further promote tumor resistance and metastatic. Herein, iRGD‐modified graphene oxide (GO) nanosheets (IPHG) are developed for the intensive treatment of metastatic tumors using focus‐specific penetrated delivery together with photothermal therapy‐mediated chemosensitization and photothermal therapy‐strengthened integrin targeting‐based antimigration. In vitro and in vivo data verified the mechanism of the tumor‐selective infiltration of IPHG is based on a rigid 2D structure‐associated advantage regarding hemodynamics and endothelial contact, followed by iRGD‐endowed transendothelial and intratumoral transport. Once IPHG‐DOX‐penetrated 4T1 tumors are exposed to near‐infrared irradiation, hyperthermia stress and photothermal therapy‐elevated effective drug concentrations result in chemosensitization and prominent tumor suppression. Meanwhile, the specific binding of iRGD to integrins and photothermal therapy leads to the synergistic perturbation of cytoskeleton remodeling and subsequent impairment of cell motility and metastasis. The tailored design of IPHG validates a promising paradigm for drug delivery to combat tumor resistance and metastasis resulting from poor target access for single chemotherapy. Abstract : 2D graphene‐oxide‐based nanoparticles IPHG‐DOX realize deep tumor penetration, profound anti‐tumor proliferation, and metastasis effects both in vitro and in vivo. iRGD and NIR irradiation synergistically induce cytoskeleton remodeling to inhibit cell motility; also, hyperthermia stress and photothermal therapy‐elevated effective drug concentrations result in chemosensitization and prominent tumor suppression.